A Focus on the Right Atrium - Rebecca K. Angoff, MD; Jonathan W. Waks, MD; Michael C. Gavin, MD, MPH; Hans F. Stabenau, MD; Jordan B. Strom, MD, MSc (JACC: Case Reports, 2023)
We report a case of a 70-year-old woman who presented for a cavotricuspid isthmus atrial flutter ablation that was aborted prematurely. On subsequent imaging, she was discovered to have a right atrial diverticulum, which was present on prior imaging but not reported, likely due to unfamiliarity with the entity. (Level of Difficulty: Intermediate.)